TRPC6 gene promoter polymorphisms in steroid resistant nephrotic syndrome children - Mahesh Kumar Kempanahalli Basappa; Prabha Senguttuvan; Ramprasad Elumalai; Bhaskar Lakkakula VKS; Soundararajan Periasamy (Society of Diabetic Nephropathy Prevention, 2015)
Introduction: Nephrotic syndrome (NS) is the most frequent cause of proteinuria in children and is emerging as a leading cause of uremia. Among idiopathic NS, 10% of children do not respond to steroids or to any other immunosuppressive therapy, and progress to end-stage renal disease (ESRD). Several studies have investigated the mutations in genes encoding podocyte proteins and their possible associations with several forms of hereditary NS. Objectives: The present study aimed to determine the distribution of the TRPC6 gene promoter polymorphisms in subjects with features of steroid resistant nephrotic syndrome (SRNS) and controls. Patients and Methods: About 49 unrelated patients with SRNS and 45 age matched controls no renal or other disorders were included in the study. PCR-RFLP was used for genotyping rs3824934 (-254C>G) and rs56134796 (-218C>T) polymorphisms located in TRPC6 gene promoter region. Results: Both -254C>G and -218C>T are polymorphic in both SRNS patients and controls. No statistically significant differences in genotypes or allele frequencies between SRNS patients and controls were observed. Linkage disequilibrium was not strong and significant and haplotypes were not associated with SRNS. Interaction analysis by multifactor dimensionality reduction (MDR) revealed a significant interaction between -254G>C and -218C>T in <10 years age group. Conclusion: The results demonstrate that the TRPC6 polymorphisms do not affect susceptibility of SRNS in Indian population. Further replications, preferably a systematic search for TRPC6 functional variants that affect gene expression are desirable for validation of our findings.